Function point analysis : - Garmus, David (Addison-Wesley, 2001)
Introduces the latest guidelines released in the International Function Point Users Group Counting Practices Manual 4.1. Fully explains the calculations and mechanics behind function point analysis as well as its most common uses. Also offers experience-based techniques for applying the methodology.